2018
DOI: 10.1016/j.jor.2018.08.039
|View full text |Cite|
|
Sign up to set email alerts
|

Clear cell sarcoma-A review

Abstract: Clear cell sarcoma (CCS) previously known as malignant melanoma (MM) of the soft tissue, although, similar in morphology to MM, contemporary histopathologic and cytogenetic techniques have made this diagnosis obsolete, as it is now possible to distinguish between CCS and MM. CCS is often diagnosed in young adults with median age of 25 years. Overall mortality is generally poor, and the 5-year survival is between 40 and 60%. Hence, early diagnosis and radical surgery are key in the treatment of this extremely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…For example, Chung and Enzinger ( 4 ) reported that 50 out of 115 patients had died from metastatic tumors in 1983. Despite progress in the different treatments available, the prognosis of patients with CCS is still poor, as 30% of patients have metastases at the time of diagnosis ( 5 ). Lymphatic metastasis is rare in other types of malignant soft tissue tumors; however, is commonly detected in CCS ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chung and Enzinger ( 4 ) reported that 50 out of 115 patients had died from metastatic tumors in 1983. Despite progress in the different treatments available, the prognosis of patients with CCS is still poor, as 30% of patients have metastases at the time of diagnosis ( 5 ). Lymphatic metastasis is rare in other types of malignant soft tissue tumors; however, is commonly detected in CCS ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common cancer types used for comparisons are shown in lavender: Lung (L), Breast (B), Colon (C), and Prostate (P). Gray zone lymphoma (#7) -lymph node; GIST (#12) -Stomach; 13 Follicular lymphoma (#13) -lymph node; Primary mediastinal lymphoma (#19) -between the 2 lungs in the mediastinum [4,[12][13][14][15][16][17].…”
Section: Somatic and Pathogenic Germline Variants Detected In The Rarmentioning
confidence: 99%
“…Clear cell sarcoma (CCS) is an extremely rare sarcoma, accounting for approximately 1% of all soft tissue sarcomas (STSs), with approximately 400 new cases in China each year. 1 , 2 CCS was originally named soft tissue melanoma because of its immunohistochemical, ultrastructural, and genomic predisposition to melanocyte differentiation. 3 , 4 This designation is now obsolete because pathologists can now accurately identify clear cell sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 This designation is now obsolete because pathologists can now accurately identify clear cell sarcomas. 1 , 5 CCS may originate anywhere in the body but more often in the extremities. The initial symptom is usually a slowly increasing painless mass with lymph node metastasis in the early to middle stages.…”
Section: Introductionmentioning
confidence: 99%